physical preparation programs on the maximumin sive power of soccer players.oxygen consumption and explo games-sideThe effect of using Small - Dahbazi, mohamed seghir; Djabali, redouane (sports creativity, 2025)
The study aims to know the effects of using the Small side-games in both the (Vo2max) and the explosion power of the football player’s lower parts, and thus to highlight the importance of the miniature games in preparing the football players. To achieve this, the researcher designed a training programme of 30 training unit . The researcher also used the training design in the single group which included 12 players chosen by the intentional method. The researcher used physical examinations in order to collect the data: Sergent test and Nevette léger test.The researcher have the reached the conclusion that the suggested programme of using the Small side-games has influence in both (Vo2max) and the explosion power of the football player’s